Analisis Komparatif Usahatani Padi Menggunakan Pola Tanam Jajar Legowo dan Pola Tanam Larikan (Studi Kasus di Kelompok Tani “Tani Jaya” di Desa Wangunrejo Kecamatan Banyuurip Kabupaten Purworejo) - Savitri, Nanda; Hasanah, Uswatun; Windani, Isna (Universitas Quality, 2025)
This study aims to determine the amount of costs, production, revenue, income, and profit in rice farming with the jajarlegowo planting pattern in Wangunrejo village, Banyuurip sub-district, Purworejo regency, determine the amount of costs, production, revenue, income, and profit in rice farming with the strip planting system in Wangunrejo village, Banyuurip sub-district, Purworejo regency, and also determine the differences between costs, production, revenue, income, and profit in rice farming using the jajar legowo planting system and the strip planting system in Wangunrejo village, Banyuurip sub-district, Purworejo regency. There are 30 farmers using the jajarlegowo planting pattern and 30 farmers using the strip planting pattern. The determination of the sample in this study used the saturated sampling method, namely all members of the population were used as samples. The amount of production costs in rice farming using the jajarlegowo planting pattern per ha is Rp 33,739,642, revenue of Rp 77,625,420, income of Rp 62,082,097 and profit of Rp 59,429,101. The amount of production costs in rice farming using the larikan planting pattern per ha is Rp 29,911,099, revenue of Rp 70,056,420, income of Rp 55,861,318 and profit of Rp 52,480,422. There are differences in production costs, revenue, income and profit in the jajarlegowo planting pattern and larikan planting pattern. The jajarlegowo planting pattern is more profitable.